SMU Students Forum Explores Why Poverty Persists in Asia and How Individuals Can Make a Difference: Part 2 - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
The Singapore Management University (SMU) chapter of AIESEC, a worldwide student organisation, together with SMU Broadcast and Entertainment hosted a panel discussion in February 2007 on the topic, “Why does poverty continue to exist in Asia and what can society do about it?” Part 2 of this two-part article provides edited excerpts of presentations by John Donaldson, SMU; Michael Switow, One Singapore and SUPERSEED; and Peter Stephens, World Bank. The panel moderator was SMU law professor Eugene Tan.